Analisis Nilai Tambah Keripik Ubi Kayu di UKM Barokah Kabupaten Bone Bolango - Supriyo Imran; Amelia Murtisari; Ni Ketut Murni (Jurnal Perspektif Pembiayaan dan Pembangunan Daerah, 2014)
This study aims to determine the Value Added Analysis of Cassava Chips in SME "Chips Barokah" Bonebolango District . This study was carried on in the village Lamahu District of Southern District Bonebolango Bulango performed on the month from October to December in 2013 . The method of analysis used in this study is the case study method is the method of data collection in a comprehensive manner , the determination of where the research is done on purpose , as for the type of data used is primary data and secondary data by recording interviews and observation techniques . Data analysis methods used are business analysis , R / C ratios for profit , efficiency and added value . The results showed that keuntunngan received from the business of processing cassava into cassava chips in five cassava production processes in SMEs " Barokah Chips " is Rp . 6.1155 million for a month , and value -added business perbahan enjoyed raw chips for SMEs Barokah 37.555/kg , this added value is the result of profit and the rest of the labor income reached 1.925 million .Keywords: Advantage , Efficient , Value Added , Cassava Chips